2011
DOI: 10.1007/s00436-011-2371-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara canis larvae reinfecting BALB/c mice exhibit accelerated speed of migration to the host CNS

Abstract: Using a small animal imaging system, migratory activity of Toxocara canis larvae stained by carboxyfluorescein succinimidyl ester (CFSE) was observed post primary infection (PPI) and post reinfection (PR) of BALB/c mice. Each infection was performed with 1,000 larvae per mouse. Primary infections were performed with labeled larvae, while for challenge infections the reinfecting larvae were stained by CFSE. The worm burden in mouse organs was determined during a period from 6 h to 21 days and 4 months PPI and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…Here it is noteworthy that in spite of a higher Th2-associated antibody response in WT mice, these displayed greater susceptibility to T. canis . These data agree with those recently reported by [18], who found that after T. canis reinfection in BALB/c mice, reinfected mice displayed significantly higher titers of T. canis -specific IgG1; moreover, those antibodies showed a greater avidity for T. canis antigens. However, re-infected mice displayed a major number of larvae in different tissues [18].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Here it is noteworthy that in spite of a higher Th2-associated antibody response in WT mice, these displayed greater susceptibility to T. canis . These data agree with those recently reported by [18], who found that after T. canis reinfection in BALB/c mice, reinfected mice displayed significantly higher titers of T. canis -specific IgG1; moreover, those antibodies showed a greater avidity for T. canis antigens. However, re-infected mice displayed a major number of larvae in different tissues [18].…”
Section: Resultssupporting
confidence: 93%
“…While widely accepted, Th2-type response in clearing helminth infections has limitations [11, 13–17], its role in mediating protection against toxocariasis in paratenic hosts is not clear, mainly because reinfection in toxocariasis favors parasite survival [18]. Recent advances in the immunobiology of T. canis indicate that regulatory mechanisms are raised after infection; mainly T regulatory cells have been involved in limiting pathologic damage by the inflammatory response [19]; however, there are few data regarding on mechanism of protection or susceptibility against such parasite.…”
Section: Introductionmentioning
confidence: 99%
“…These events might be multifocal trauma, hypoxia and accumulation of macrophages. After oral infection, Toxocara larvae reach the brain as early as 60 h later by perforating vessel walls (Kolbeková et al 2011). Subsequent haemorrhages and tissue migration lead to parenchymal damage (Cardillo et al 2009;Janecek et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The result of the present study are according to Fenoy et al (2008) that found high-avidity of IgG antibodies (over 50%) 60 days post-infection of BALB/c with 1000 T. canis eggs. However, another study using BALB/c mice reported high-avidity of IgG antibodies at only 30 days post-infection of 1000 larvae (KOLBEKOVÁ et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Studies using the ELISA immunoassay with urea, a denaturant agent that can dissociate the antigen-antibody interaction when the avidity is low (BERTOZZI et al, 1999), have been conducted to measure the IgG avidity percentage in human toxocariasis (HUBNER et al, 2001;ELEFANT et al, 2006). In experimental model, only two studies on avidity of specific IgG against TES were done (FENOY et al, 2008;KOLBEKOVÁ et al, 2011). The aim of this study is to investigate the applicability of indirect ELISA, associated with urea, to discriminate between the stages of toxocariasis infection in experimentally infected BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%